2019
DOI: 10.1124/jpet.118.255661
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Testing of Nalfurafine as an Opioid-sparing Adjuvant that Potentiates Analgesia by the Mu Opioid Receptor-targeting Agonist Morphine

Abstract: Mu opioid receptor (MOR)-targeting analgesics are efficacious pain treatments, but notorious for their abuse potential. In preclinical animal models, coadministration of traditional kappa opioid receptor (KOR)-targeting agonists with MOR-targeting analgesics can decrease reward and potentiate analgesia. However, traditional KOR-targeting agonists are well known for inducing antitherapeutic side effects (psychotomimesis, depression, anxiety, dysphoria). Recent data suggest that some functionally selective, or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 85 publications
(132 reference statements)
5
32
0
Order By: Relevance
“…agonists (DiMattio et al, 2015;White et al, 2015;Dunn et al, 2018Dunn et al, , 2019Ho et al, 2018;Kaski et al, 2019;Mores et al, 2019). In addition, a recent paper showed low intrinsic efficacy, rather than G-protein bias, could explain the reduced respiratory side effects in MOPr agonists (Gillis et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…agonists (DiMattio et al, 2015;White et al, 2015;Dunn et al, 2018Dunn et al, , 2019Ho et al, 2018;Kaski et al, 2019;Mores et al, 2019). In addition, a recent paper showed low intrinsic efficacy, rather than G-protein bias, could explain the reduced respiratory side effects in MOPr agonists (Gillis et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, the biased agonist RB-64, showed no sedation, motor incoordination, or anhedonia-like effects in mice ( White et al, 2015 ) and the only clinically available KOPr agonist, nalfurafine, has been shown to be extremely G-protein biased ( Schattauer et al, 2017 ). However, few reports have fully explored biased signaling at KOPr and correlated this to antinociceptive effects and side effects in structurally similar agonists ( DiMattio et al, 2015 ; White et al, 2015 ; Dunn et al, 2018 , 2019 ; Ho et al, 2018 ; Kaski et al, 2019 ; Mores et al, 2019 ). In addition, a recent paper showed low intrinsic efficacy, rather than G-protein bias, could explain the reduced respiratory side effects in MOPr agonists ( Gillis et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although weaker evidence of punishment was observed with nalfurafine based on statistical analysis, the overall findings were consistent with a recent report of contingently administered nalfurafine and salvinorin A decreasing rates of oxycodone self-administration under a progressive-ratio schedule of reinforcement in rhesus monkeys (Zamarripa et al 2020). Considered alongside reports that nalfurafine and other G-protein biased KOR agonists attenuate the conditioned rewarding effects of MOR agonists (Kaski et al 2019; Tsuji et al 2001), these results suggest that the abuse-limiting effects of KOR agonists may be G-protein mediated. Furthermore, in light of evidence that the aversive effects of KOR agonists are beta-arrestin mediated (Bruchas and Chavkin 2010; Bruchas et al 2007), these results also suggest that aversion may not be a necessary component of KOR-mediated punishment.…”
Section: Discussionmentioning
confidence: 67%
“…Many studies have sought to measure the bias factor, to understand the lack of sideeffects traditionally associated with KOPr agonists, however, there have been mixed results (Table 1). In human embryonic kidney-293 (HEK293) cells, nalfurafine was a G-protein biased agonist compared to U50,488 (Kaski et al, 2019), with moderate G-protein bias at the rat KOPr and extreme G-protein bias at the human KOPr (Schattauer et al, 2017).…”
Section: Nalfurafinementioning
confidence: 99%
“…2). Mesyl SalB and EOM are G-protein biased at the human KOPr using U50,488 as a reference ligand (Kivell et al, 2018;Kaski et al, 2019). However, EOM SalB was also found to be β-arrestin biased at the mouse KOPr with dynorphin A 1-17 as the reference ligand (DiMattio et al, 2015).…”
Section: Salvinorin a Analoguesmentioning
confidence: 99%